State of art About the school adaptation process In children under 3 years old - Burneo Farfán, Laura Elena (2020)
IThe objective of this article is to disseminate outstanding research that has been carried out during the last ten years in the field of the School Adaptation Process for children under 3 years. This is a critical period to which our children are exposed given the increasing participation of women in the workplace. This process explains the child's transition from a home life with personalized attention from parents or substitutes surrounded by much affection for an educational environment. In this work a review of the subject is made by dividing it into four factors that can determine the quality of such adaptation: family overprotection of the child, child attachment, change of environment, and the role of parents. This data is expected to be useful for researchers interested in exploring, describing, correlating, and explaining the socio-emotional dynamics in which this interesting period unfolds in people's lives.